1990
DOI: 10.1177/028418519003100408
|View full text |Cite
|
Sign up to set email alerts
|

CT Demonstration of Fistulae in Patients with Gynecologic Neoplasms

Abstract: Ten women treated for gynecologic neoplasms (8 cervical carcinomas, one vaginal and one endometrial carcinoma) were found at computed tomography (CT) to have a fistula although only 5 patients had symptoms that could be related to a fistula. Five women had vesico-vaginal fistulae, 2 recto-vaginal, 2 entero-cervical and one a vulvo-pubical fistula. Three patients had recurrent malignancy at the CT examination. We regard CT as the ragiologic method of choice in diagnosing gynecologic fistulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Traditionally, urogenital fistulas were explored by excretory urography or retrograde cystography [4,5]. With the evolution of CT and the emerging utilization of MDCT in everyday clinical practice, it has been found that MDCT is a more sensitive and specific technique in the detection and precise anatomic delineation of these rare pathologic abnormalities compared with conventional radiology modalities [6,7]. Moving one step forward, we initiated a new protocol combining CT cystography and intravaginal neutral contrast agent.…”
mentioning
confidence: 99%
“…Traditionally, urogenital fistulas were explored by excretory urography or retrograde cystography [4,5]. With the evolution of CT and the emerging utilization of MDCT in everyday clinical practice, it has been found that MDCT is a more sensitive and specific technique in the detection and precise anatomic delineation of these rare pathologic abnormalities compared with conventional radiology modalities [6,7]. Moving one step forward, we initiated a new protocol combining CT cystography and intravaginal neutral contrast agent.…”
mentioning
confidence: 99%
“…Beyond this clinical impression, imaging has been used to define the fistula and assess the state of underlying disease. Frequently, several imaging modalities are required including contrast studies (barium enemas, small bowel series, intravenous pyelography, cystogram and vaginography) ( 3 ) and CT scanning ( 4 , 5 ) .…”
mentioning
confidence: 99%